Is there a real difference in approach between women and men with non-ST-segment elevation myocardial infarction? Insights from a multicentre national registry. (14th October 2021) - Cabral, M; Fernandes, S; Santos, L G; Carvalho, M; Carvalho, R; Santos, B; Loureiro, M F; Morais, J
Abstract:  : In patients with non-ST-elevation myocardial infarction (NSTEMI), the early invasive strategy has shown benefit in morbidity and mortality, especially in intermediate-to-high risk patients. However, women still seem to have a lower revascularization rate, regardless of the risk. The aim of this study is to describe our clinical practice reality about the performance of the invasive strategy between genders among NSTEMI patients, in Portugal. The authors performed a retrospective analysis of patients admitted with NSTEMI included in the Portuguese Registry on Acute Coronary Syndromes (ProACS) between October 2010 and February 2021. A propensity score matching included baseline characteristics and previous history was applied. Comparison tests and log-rank test were performed. A p-value less than 0.05 was considered statistically significant. A total of 11858 patients with NSTEMI were included, of which 71.3% (n=8450) were men. After the propensity score performing, 4458 patients were analysed, 50.0% (n=2229) men. Table 1 shows the most important baseline characteristics. The authors found a significant delay in hospital admission after the onset of symptoms in women (median of 6 hours and 48 minutes) compared to men (median of 5 hours) (p<0.01). Grace score was higher in males (mean 153 points) than in females (mean 145 points) (p<0.01). The cardiac catheterization was performed in 82.9% (n=3695) of the patients, with no difference between genders (p-value=0.19), as shown in table 2. Among those who underwent cardiac catheterisation, the presence of significant stenosis and coronary occlusion was greater in males, for almost all localizations. The absence of obstructive coronary lesions was more common in females (p-value<0.01). During hospitalization, sustained ventricular tachycardia was more prevalent in males (p-value =0.01), with no significant difference for other complications or in-hospital mortality. A 1-year follow-up of 2351 patients (1184 men and 1163 women) was analysed, with survival of 91.2% (n=1080) in men and 91.0% (n=1056) in women, with no significant difference (p-value=0.80). In conclusion, we observed that women are admitted to the hospital later than men and have a lower Grace score at admission. However, the standardized analysis of the groups allows us to infer that the invasive strategy does not seem to be less frequent or late in women, as observed in other populations. A more recent analysis, including risk groups, would be interesting to clarify the results. Funding Acknowledgement: Type of funding sources: None.